Temperature dependence of the cooperative out-of-equilibrium elastic switching in a spin-crossover material. Issue 12 (11th March 2019) - Bertoni, Roman; Collet, Eric; Cailleau, Hervé; Boillot, Marie-Laure; Tissot, Antoine; Laisney, Jérôme; Enachescu, Cristian; Lorenc, Maciej
Abstract : We explore the key parameters that influence the efficiency of the cooperative low-spin to high-spin conversion through long range elastic intermolecular interactions during the so-called elastic step, triggered by instantaneous photo-induced conversion. Abstract : We present a study of a molecular material, [Fe iii (3-MeO-SalEen)2 ]PF6, undergoing cooperative reversible photo-induced transition between low-spin state and high-spin state. By using temporally multiscale pump–probe laser spectroscopy, we explore the key parameters that influence the low-spin to high-spin conversion efficiency through long range elastic intermolecular interactions during the so-called elastic step, where crystalline volume expansion takes place. We rationalize our findings using Monte Carlo simulations, and a mechano-elastic model. The experimental results and the simulations support the existence of a fast mechanism by which molecules cooperatively switch through coupling to the lattice strain. The efficiency of the coupling process is shown to depend on several parameters including the initial thermal population and the instantaneous photo-induced population among others. Far below the crossover temperature, the elastic self-amplification occurs above a threshold photo-excitation. On approaching the thermal crossover, the threshold disappears and the photo-elastic conversion increases.